Aesthetical Value in V. Seseman’s Philosophical Conception - Mureika, Juozas (Problemos, 1979)
A dialectical character of the approach to aesthetical value in philosophy by V. Seseman (1884-1963), a professor at Vilnius University, is revealed in the article. Pointing out the originality of his philosophical conception, the latter is characterized as a dialectical anthropology or anthropologized dialectical materialism.